From Palace to Public Sphere: Historical Trajectories of the Pajoge Dance as a Bugis Performing Arts Identity (1880–1941) - Shafa Nurazizah; Asep Imansyah; Marsella Yulistiani (Jurnal Ilmiah Multidisiplin, 2026)
The background of this research stems from cultural issues in Indonesia, which still tend to be consumptive in nature, with art often viewed merely as entertainment without considering its historical value. This condition opens up space for research to examine how colonialism influenced the form, function, and public perception of Pajoge dance, particularly in Bone between 1880 and 1941. This study aims to explain the dynamics of change in Pajoge dance, which underwent significant transformation when performed outside the palace environment. This study uses the historical method proposed by Sartono Kartodirdjo, through the stages of heuristics, source criticism, interpretation, and historiography. The analysis is reinforced by Parsons' structural functionalism to understand the role of Pajoge in building Bugis cultural identity. The results of the study show that Pajoge initially functioned as a symbol of status and legitimacy of palace power, but underwent a transformation when performed in public spaces due to political intervention and social change. The study recommends the need to recontextualize Pajoge as a cultural heritage that reflects the historical dynamics and identity of the Bugis.